2017
DOI: 10.1111/imm.12776
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐dihydroxyvitamin D3‐induced dendritic cells suppress experimental autoimmune encephalomyelitis by increasing proportions of the regulatory lymphocytes and reducing T helper type 1 and type 17 cells

Abstract: Dendritic cells (DCs), a bridge for innate and adaptive immune responses, play a key role in the development of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE), an animal model for MS. Administration of tolerogenic DCs has been used as an immunotherapy in autoimmune diseases. Deficiency of vitamin D is an environmental risk factor of MS. In this study, we induced tolerogenic DCs by 1,25-dihydroxyvitamin D and transferred the tolerogenic DCs (VD -DCs) into EAE mice by adoptive transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 34 publications
(45 reference statements)
2
53
0
Order By: Relevance
“…The decreased expansion of antigen-specific T cells regulated by DCregs is critical in the control of autoimmune diseases (Piemonti et al, 2000). Several studies have suggested that the inhibition of antigen-specific T cells can ameliorate disease severity in EAE mice (Serada et al, 2008;Yoshida et al, 2013;Xie et al, 2017). In this study, the co-culture experimental results confirm the conjecture that K313-modified DCregs significantly suppress the expansion of OVA 323-339 peptide-specific CD4+ T cells.…”
Section: Discussionsupporting
confidence: 76%
“…The decreased expansion of antigen-specific T cells regulated by DCregs is critical in the control of autoimmune diseases (Piemonti et al, 2000). Several studies have suggested that the inhibition of antigen-specific T cells can ameliorate disease severity in EAE mice (Serada et al, 2008;Yoshida et al, 2013;Xie et al, 2017). In this study, the co-culture experimental results confirm the conjecture that K313-modified DCregs significantly suppress the expansion of OVA 323-339 peptide-specific CD4+ T cells.…”
Section: Discussionsupporting
confidence: 76%
“…injection of tDCs was not the right way of application, although it was shown in an EAE model that i.v. injection of tDCs led to a decrease in clinical symptoms in the mice [318,319]. Another study shows that i.p.…”
Section: Transfer Of Vitd3 and Dex-modulated Dcs Carrying Hcyp2d6peptmentioning
confidence: 94%
“…Mature DCs are uniquely capable of activating naïve T cells through their high and dense expression of membrane-bound costimulatory molecules such as CD40, CD80, and CD86 and the soluble costimulatory signal IL-12. Immature dendritic cells possess ability to induce immunological tolerance through their high levels of co-inhibitory molecules such as IL-10 and PD-L1 (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94). Given that fibroblasts are associated with post-injury healing, and that upregulation of immune inhibitory molecules is known to occur in the healing phase of injury, we sought to investigate whether DC maturation was altered by fibroblasts using a co-culture system.…”
Section: Inhibition Of Dendritic Cell Maturation By Fibroblastsmentioning
confidence: 99%